A young woman with right upper quadrant pain. Issue 2 (March 2019) - Lee, Sun Hwa; Yun, Seong Jong
Patients with right upper quadrant pain are commonly encountered in the emergency department. The causes of right upper quadrant range from infection or inflammation to malignancy. Thus, prompt and accurate diagnoses are essential in the emergency department. However, vicarious excretion of contrast media via the gallbladder, presenting as right upper quadrant pain, has been rarely reported and is not well known. The present case is instructive because gallbladder opacification is often considered a pathologic condition in patients with right upper quadrant pain. Although vicarious excretion via the gallbladder is uncommon in patients with right upper quadrant pain, inaccurate or delayed diagnoses may prolong hospitalization and increase medical costs due to unnecessary and invasive diagnostic procedures.